Effects of combining some theoretical models in the cross-section calculations of some alpha-induced reactions for natSb. (August 2022) - Şekerci, M.; Özdoğan, H.; Kaplan, A.
Abstract: In cases where it is not possible to obtain the cross-section values experimentally due to various factors, the importance of obtaining them with theoretical models has been explained in many studies available in the literature. In this context, the comparison of the cross-section values obtained by using the theoretical models with the experimental data will also be very beneficial for updating and developing these models. Existing studies, which also serve this purpose, have given inspiration to this study and it is aimed to examine the effects of the simultaneous use of the alpha optical model potentials and the level density models on the cross-section calculations for some alpha-particle-induced reactions on natural antimony. The effects of theoretical models on the cross-section calculations were investigated by comparing the obtained calculation results with the experimental data taken from the literature. The TALYS code, which is frequently preferred in the literature, was used in all calculations within the scope of this study. For the comparison of the calculated results with the experimental data, not only a visual analysis by graphing the outcomes, but also a mean-weighted-deviation calculation was used, and the findings were interpreted by accounting for both of them. Highlights: Cross-section calculations were done for nat Sb(α, x) 121, 123-126 I reactions. TALYS 1.95 code was used for the calculations. Alpha optical model potentials and level density models were used in calculations. Calculation results and available experimental data from the literature were compared. The outcomes were compared both visually and numerically using visuals and a mean-weighted-deviation.